Association between dietary intake and bone density among female Students at Imam Abdulrahman Bin Faisal University, Saudi Arabia - Alyami, Seham H.; Alqahtani, Maha J.; Alsadah, Hawra H.; Altumaysi, Nouf A.; Abuzaid, Omar I.; Goja, Arafat M. (International Journal Of Community Medicine And Public Health, 2019)
Background: Recently, new studies have shown that the prevalence of osteoporosis and related fractures has been increased among young females. This study aimed at finding out the association between dietary intake and bone mineral density (BMD) among university Saudi female students at Imam Abdulrahman Bin Faisal University. Methods: A cross sectional study was carried out on 104 females’ students aged 18-24 years taken randomly from Rakkah campus. Dual X-ray absorptiometry was used to evaluate BMD and body composition. A complete and valid questionnaire was used to collect the required information about socio-economic status, lifestyle, body measurements, health history data, and food habits as well as food frequency questionnaire was also used. The results were statically analyzed (SPSS, 2015 V, 23) and descriptive statistics Chi-square test and independent samples t- test were used for the statistical analysis. Results: The results demonstrated that the majority (65%) of students have normal body mass index (18.5-24.9 kg/m2), 58% normal BMD (>-1.0 SD) and 42% have low BMD. Among the low BMD students, 4% having osteoporosis (<-2.5 SD). In the present study, 36.5%, 30.8%, 37.5% and 36.5 % of student with high BMD consumed full fat dairy products, milk, yogurt, laben, cheese, respectively, compared with 21.2%, 19.2%, 245, 29.8% of students with low BMD. Conclusions: Higher intakes in dairy products were associated with students’ bone health. Therefore, students should be more aware of their bone health and increase their knowledge regarding protective dietary foods for bone development.